2011
DOI: 10.2478/s11686-011-0064-4
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and lead concentrations in Moniliformis moniliformis (Acanthocephala) and Rodentolepis microstoma (Cestoda), and in their definitive hosts, Rattus rattus and Mus domesticus in El Hierro (Canary Archipelago, Spain)

Abstract: Information on parasites of vertebrates living in terrestrial ecosystems as monitoring tools for heavy metal environmental pollution is scarce. The present study evaluates the potential suitability of the models Rattus rattus/Moniliformis moniliformis and Mus domesticus/Rodentolepis microstoma as promising bioindicator systems for cadmium and lead pollutions under natural conditions. The highest level of cadmium was found in one specimen of M. moniliformis (335.2 ng g -1 wet weight) and the average concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Generally, with the similar fresh weight, H. diminuta accumulates up to 3-fold portion of ingested Pb dose compared with that of the host most loaded soft tissue (kidney) at both exposure levels. Therefore, our research clearly confirmed hyper-accumulative properties of H. diminuta for Pb, and the Hymenolepid tapeworm could serve as a suitable accumulative indicator of environmental pollution as introduced by Torres et al (2011) and Sures et al (2002, 2003 b ). Unlike field studies, we were able to determine the exact Pb-dose portion stored in fresh tapeworm tissue which was 0·015 and 0·037% after low and elevated exposure, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Generally, with the similar fresh weight, H. diminuta accumulates up to 3-fold portion of ingested Pb dose compared with that of the host most loaded soft tissue (kidney) at both exposure levels. Therefore, our research clearly confirmed hyper-accumulative properties of H. diminuta for Pb, and the Hymenolepid tapeworm could serve as a suitable accumulative indicator of environmental pollution as introduced by Torres et al (2011) and Sures et al (2002, 2003 b ). Unlike field studies, we were able to determine the exact Pb-dose portion stored in fresh tapeworm tissue which was 0·015 and 0·037% after low and elevated exposure, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…The tapeworms of the genus Hymenolepis, which parasitize rodents, were also subjected to tests. After exposure to Pb under laboratory conditions, parasites contained the metal in amounts 17 times higher than those found in rat kidneys [7,17].…”
Section: Discussionmentioning
confidence: 93%